Analisis Yuridis Konsolidasi Tanah Masyarakat Hukum Adat di Daerah Perkotaan - Khadijah, Siti Nur; Idham, Idham (ARBITER: Jurnal Ilmiah Magister Hukum, 2021)
The existence of customary land rights in Article 3 of the Basic Agrarian Law is a common thing, because along with the territorial rights of indigenous peoples, they existed before the formation of the Republic of Indonesia. However, many problems with land in customary areas that arise in territorial and national sizes will never get a complete settlement without the fair treatment needed as a benchmark for determining the existence of customary rights and their implementation. The existence criteria for establishing customary rights consist of three elements, namely the existence of certain customary rights into the environment, the existence of certain customary law communities, and the purpose of taking the lives of indigenous peoples, and the existence of customary law regarding the maintenance of order, the use of controversial lands that apply and are adhered to by the government. culture. In this study using a normative juridical method. The results of this study show that there are still rules from the community, and there is no regulation on ulayat rights. Customary rights regulations can be a loophole for customary rights, even at the lowest level.